The Relationship between Civil Society Organization and Political Party in Legislative Election: The Case of of Fatayat and PKB in Indonesia - M. Anas Mahfudhi; Aditya Perdana (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article aims to analyze the political strategies of Fatayat as a civil society organization to win women candidates in the 2019 legislative elections. To do so, it uses two concepts of Gwendolyn Bevis’s theory of civil society and political parties which emphasizes constructive relationships between civil society organizations and political parties, and Peter Schroder’s theory on political strategies and tactics to win female candidates of legislative elections. This article uses a qualitative method and collects the data through interview techniques. The result of this study indicates that the relationship between Fatayat and PKB (Partai Kebangkitan Bangsa) runs constructively for both have a shared history. This constructive relationship can also be applied to explain the political dynamic within Nahdlatul Ulama (NU). This article concludes that the Fatayat’s strategy to win women candidates in the legislative elections was supported by a constructive relationship between Fatayat and PKB.  This finding contributes to the study of the relationship between civil society organizations and political parties.